2017
DOI: 10.1007/s12094-016-1599-5
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNAs in liquid biopsies: future biomarkers for prostate cancer

Abstract: Prostate cancer is the second most diagnosed cancer in males in the world. Plasma quantification of prostate-specific antigen substantially improved the early detection of prostate cancer, but still lacks the required specificity. Clinical management of prostate cancer needs advances in the development of new non-invasive biomarkers, ameliorating current diagnosis and prognosis and guiding therapeutic decisions. microRNAs (miRNAs) are a class of small non-coding RNAs that regulate gene expression at the post-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 76 publications
0
40
0
1
Order By: Relevance
“…Recent expression profiling studies in PCa suggest that miR may serve as potential biomarkers for PCa risk and disease progression (26)(27)(28)(29)(30). Growing evidence has indicated that mutation or polymorphisms in miR genes could affect target-binding activity, expression or processes of mature miR, consequently affecting the expression of their target genes (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Recent expression profiling studies in PCa suggest that miR may serve as potential biomarkers for PCa risk and disease progression (26)(27)(28)(29)(30). Growing evidence has indicated that mutation or polymorphisms in miR genes could affect target-binding activity, expression or processes of mature miR, consequently affecting the expression of their target genes (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, tumor-derived EVs presence in body fluids makes them a promising source of cancer biomarkers. EVs miRNA signatures already proved to have prognostic value in several cancer types, including colorectal cancer (Fu et al, 2018), pancreatic cancer (Goto et al, 2018), prostate cancer (Valentino et al, 2017), non-small cell lung cancers (Liu et al, 2017), and glioblastoma (Skog et al, 2008). A novel approach using organoid media supernatant has been proposed for the identification of EVs proteins present exclusively in the blood of PDAC patients, and not in patients disease-free or with benign conditions (Huang et al, 2019).…”
Section: New Horizons Of Organoids Application: Modeling Evs Releasementioning
confidence: 99%
“…Such species are enriched in exosomes and strongly resist RNases. High levels of exosomes are found in several bodily fluids from cancer patients [32] and because of their resistant nature, exosomes and miRNA can be isolated from biofluid samples and stored for many years in the freezer [33]. Their composition seems to reflect that of the parental cells and therefore provide a novel type of biomarker for various patient scenarios [34].…”
Section: Exosomes and Circulating Rnamentioning
confidence: 99%